Quantification of oteseconazole in rat plasma using LC-MS/MS and its application to pharmacokinetic study - Susararla, Krishna Phani Chandra; Shelke, Om; Shorgar, Neetu (Creative Pharma Assent, 2024)
Background: Oteseconazole is a new molecule launched for human treatment. However, the information is not available in the public domain for analyzing blood samples. This study describes the method development and validation using LC-MS/MS to measure the concentration of Oteseconazole in rat plasma. Methodology: The analysis method was developed using a phenyl column, which was utilized to accomplish separation. Furthermore, the mobile phase was a combination of acetonitrile and 0.1% formic acid in water, with a ratio of 30:70 (v/v). The sample was introduced into the system at a 1.0 mL/min flow rate, and the injection volume was 10 μLand analyzed for five minutes using mass spectrometer +ESI mode. Results and discussion: MRM is used to quantify Oteseconazole and Posaconazole by analyzing the transitions of their respective m/z values. The concentration ranges of Oteseconazole were 5-100 ng/mL. The correlation coefficient of Oteseconazole was found to be 0. 999. HQC, MQC, LQC, and LLQC precision and accuracy were determined to be 98.60%, 98.69%, 96.11%, and 94.48%, respectively. Respectively, the accuracy recovery of Oteseconazole was determined to be 97.48%. In pharmacokinetic studies, it was observed that Oteseconazole exhibited an average AUC0-t value of 1386 ng-hr/ml and a Cmax value of 44.864 ng/ml in rats. Conclusion: The validated approach has effectively demonstrated the determination of pharmacokinetic parameters after the oral administration of Oteseconazole in Wister rats.